Membrane Bioreactor–Treated Domestic Wastewater for Sustainable Reuse in the Lake Victoria Region. (16th June 2020) - Gukelberger, Ephraim; Atiye, Talha; Mamo, Julian A; Hoevenaars, Kyra; Galiano, Francesco; Figoli, Alberto; Gabriele, Bartolo; Mancuso, Raffaella; Nakyewa, Pauline; Akello, Francis; Otim, Robert; Mbilingi, Bwambale; et al.
ABSTRACT: Lake Victoria is a shared water resource between Kenya, Uganda, and Tanzania, which is the second largest freshwater lake in the world. It has long since suffered from the consequences of overexploitation of its resources, mainly fish stocks, and increasingly high pollution. The closure of 58% of the fish processing plants (FPPs) is attributed to the declining fish stocks due to overfishing and pollution in particular. The installation and operation of a pilot membrane bioreactor (MBR) in Kisumu, Kenya, adopts an integrated approach by providing an integral, sustainable, cost‐effective, and robust solution for water sanitation, which also meets the demand for clean water in the fish processing industry, aquaculture, and irrigation. The innovative system comprises a pilot MBR coupled with a recirculation aquaculture system (RAS). The RAS is able to recirculate 90% to 95% of its water volume; only the water loss through evaporation and drum filter back flushing has to be replaced. To compensate for this water deficit, the MBR treats domestic wastewater for further reuse. Additionally, excess purified water is used for irrigating a variety of local vegetables and could also be used in FPPs. The pilot‐scale MBR plant with around 6 m 2 submerged commercial polyethersulfone (PES) membranes provides treated water in basic agreement with Food and Agriculture Organization (FAO) standards for irrigation and aquaculture, showing no adverse effects on tilapia fingerlings production. A novel membrane module with a low‐fouling coating is operating stably but has not yet shown improved performance compared to the commercial one. Integr Environ Assess Manag 2020;16:942–954. © 2020 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC) KEY POINTS: A pilot‐scale membrane bioreactor (MBR) with 6.25‐m 2 membrane area of submerged flat polyethersulfone (PES) membranes successfully treated domestic wastewater at Lake Victoria, Kisumu, Kenya. Part of the PES membranes were coated with a novel low‐fouling layer, and performance was compared in parallel with the commercial ones. The treated wastewater was successfully used to top up water loss in a recirculating aquaculture system (RAS) cultivating tilapia fingerlings. Application of MBRs in wastewater treatment shows promising application not only for RAS but also for treatment of fish processing wastewater in the Lake Victoria region.